Działalność bibliotekarska i bibliofilska profesora Kazimierza Kaczmarczyka (1878-1966), dyrektora Archiwum Państwowego w Poznaniu - Matysiak, Jarosław (Biblioteka Uniwersytecka w Poznaniu, 2011)
Artykuł przedstawia działalność zasłużonego archiwisty i historyka, długoletniego dyrektora Archiwum Państwowego w Poznaniu, prof. dra Kazimierza Kaczmarczyka (1878-1966) w Poznańsko-Pomorskim Kole Związku Bibliotekarzy Polskich, w Związku Bibliotekarzy Polskich Koło Poznańskie, Związku Bibliotekarzy i Archiwistów Polskich Koło Poznańskie oraz w Stowarzyszeniu Bibliotekarzy Polskich Okręg Poznański do roku 1939 oraz w latach 1945–1966. Wspomniano także o udziale Kaczmarczyka w pracach poznańskiego Towarzystwa Bibliofilów Polskich w latach 1924-1939. W artykule omówiono jego księgozbiór oraz starania o sprzedanie książek Wydziałowi Humanistycznemu Uniwersytetu Marii Curie-Skłodowskiej w Lublinie, a następnie Bibliotece Katolickiego Uniwersytetu Lubelskiego.

This article describes the work of the distinguished archivist and prominent historian Prof. Kazimierz Kaczmarczyk (1878-1966), a long time director of the State Archives in Poznań, in the Poznań-Pomorze Polish Librarians Union, the Poznań branch of the Polish Librarians and Archivists Union and in the Poznań branch of the Polish Librarians Association until 1939 and in the post-war years of 1945–1966. Prof. Kaczmarczyk’s participation in the works of the Poznań-based Association of Polish Bibliophiles between 1924 and 1939 is also briefly mentioned. The article discusses a vast collection of books that belonged to the Professor and the attempts to sell these holdings to the faculty of the Humanities of M. Curie-Skłodowska University in Lublin and later to the library of the Catholic University in Lublin.
The library and bibliophilic activity of Prof. Kazimierz Kaczmarczyk (1878-1966), director of the State Archives in Poznań
Keywords: archiwum; archive; bibliotekoznawstwo; library studies; bibliofilstwo; bibliophily; Stowarzyszenie Bibliotekarzy Polskich; Polish Librarians Association